(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This research investigates the contemporary use of archaic phraseological units as vehicles for expressing "historical memory" in French and Uzbek languages. Examining various types of phraseological units within the context of "historical memory" in linguistics, our findings reveal that archaic expressions continue to be employed by linguists in both linguistic traditions. The study emphasizes the structural nuances of archaic words in phraseology, a focal point that garnered attention, especially in the early 21st century. While archaism has been extensively explored in English and Russian linguistics, this research addresses the notable gap in studying archaic expressions related to “historical memory” in the French and Uzbek languages. By bridging this gap, the study contributes to a deeper understanding of the linguistic manifestations of historical consciousness in these two distinct traditions.